Prevalence and antibiotic sensitivity patterns of extended-spectrum beta-lactamase-producing Klebsiella pneumoniae in pneumonia patients at Ngoerah Hospital from 2020 to 2022 - Arikandini, Dewa Ayu Putu Aisaka Rajeshi; Ni Nyoman Sri Budayanti; Ni Nengah Dwi Fatmawati; I Putu Bayu Mayura (Journal of Clinical Microbiology and Infectious Diseases, 2025)
Background: Pneumonia remains a major global cause of mortality, with Klebsiella pneumoniae recognized as a significant pathogen. The emergence of antibiotic resistance, particularly due to Extended-Spectrum Beta-Lactamase (ESBL) production by K. pneumoniae, complicates treatment efforts. This study aimed to determine the prevalence of ESBL-producing K. pneumoniae in pneumonia patients and assess its antibiotic sensitivity profile. Methods: A descriptive cross-sectional study was conducted retrospectively using secondary data from VITEK 2 Compact (bioMérieux) laboratory results on sputum samples collected from pneumonia patients at Ngoerah Hospital from 2020 to 2022. A total of 515 samples met the inclusion criteria out of 1,350 tested. Results: ESBL-producing K. pneumoniae was identified in 305 isolates (59.2%), with yearly prevalence rates of 63% in 2020, 52% in 2021, and 61% in 2022. Most patients were male (66.6%), aged 60 years or older (40%), and treated in non-ICU settings (69.2%), with expectorated sputum as the most common specimen type (63%). Antibiotic sensitivity testing revealed high susceptibility of ESBL-producing isolates to ertapenem (100%), meropenem (100%), amikacin (93%), and tigecycline (81%). Conclusion: ESBL-producing K. pneumoniae accounted for over half of pneumonia cases, with fluctuating prevalence across the study period. The infection predominantly affected older male patients treated in non-ICU wards. Despite resistance to many beta-lactam antibiotics, high sensitivity to carbapenems and other specific agents highlights their continued relevance in treatment. Surveillance of antibiotic resistance patterns remains essential for effective clinical management.